1979
DOI: 10.1126/science.373119
|View full text |Cite
|
Sign up to set email alerts
|

"Spontaneous" Neoplastic Transformation in Vitro: a Form of Foreign Body (Smooth Surface) Tumorigenesis

Abstract: Explants of subcutaneous connective tissue from adult BALB/c mice into plastic petri dishes were serially subcultured and tested for tumorigenicity in two ways: by the subcutaneous implantation of cells attached to plastic plates (1 by 5 by 10 millimeters), and by the subcutaneous injection of cells suspended in saline. Cells grown in vitro for 18 or more days before being implanted attached to a plastic plate (2.4 x 10(4) to 3.4 x 10(5) cells per plate) formed tumors after 24 to 79 weeks. The latent period be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

1980
1980
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…However, this possibility was low 6 ; (iii) culture medium contained carcinogenic substances 7 ; (iv) culture dish secreted carcinogenic substances. 8 Heppner, one of their contemporary researchers, speculated that inflammation was one of the possible causative factors for foreign-body-induced tumorigenesis. 77 Since then, we have expanded the experimental systems and demonstrated that foreign-body-induced inflammation and its-derived ROS are definitely the cause for the conversion.…”
Section: Experimental Models Of Foreign-body-induced Carcinogenesis Amentioning
confidence: 99%
See 2 more Smart Citations
“…However, this possibility was low 6 ; (iii) culture medium contained carcinogenic substances 7 ; (iv) culture dish secreted carcinogenic substances. 8 Heppner, one of their contemporary researchers, speculated that inflammation was one of the possible causative factors for foreign-body-induced tumorigenesis. 77 Since then, we have expanded the experimental systems and demonstrated that foreign-body-induced inflammation and its-derived ROS are definitely the cause for the conversion.…”
Section: Experimental Models Of Foreign-body-induced Carcinogenesis Amentioning
confidence: 99%
“…[4][5][6] They showed that cells of nontumorigenic but immortalized mouse cell lines or freshly isolated connective tissues from mice were converted into lethally growing tumors of monoclonal origin in mice after they were implanted, being attached to foreign bodies. 4,5,8,9 They suggested at least 5 causes for the conversion: (i) immortalized cells acquired preneoplastic phenotype for the lack of anchorage-independent growth property, and thus the substrate-attached cells grew exponentially in vitro and lethally in vivo 4,5 ; (ii) activation of endogenous oncornaviruses. However, this possibility was low 6 ; (iii) culture medium contained carcinogenic substances 7 ; (iv) culture dish secreted carcinogenic substances.…”
Section: Experimental Models Of Foreign-body-induced Carcinogenesis Amentioning
confidence: 99%
See 1 more Smart Citation
“…The malignant conversion is not restricted to mouse cells; we also observed the same phenomenon in human colonic adenoma cells [53] or in rat regressive mammary tumor cells [54]. The concept of the foreign body-induced carcinogenesis was established by Boone & Takeichi [55]. They attached immortalized but non-tumorigenic mouse fibroblast cell lines to a piece of plastic plate or glass beads and implanted them into a subcutaneous space in mice; then the fibroblast cells were converted into tumorigenic ones.…”
Section: Phagocytes As a Driving Force For Inflammation-based Carcinomentioning
confidence: 86%
“…They attached immortalized but non-tumorigenic mouse fibroblast cell lines to a piece of plastic plate or glass beads and implanted them into a subcutaneous space in mice; then the fibroblast cells were converted into tumorigenic ones. First, they speculated that some carcinogenic chemical substances were diffused by the foreign body [55]. Heppner, a contemporary researcher, speculated that foreign-body-induced inflammation was one of the possible causative factors for the conversion [56].…”
Section: Phagocytes As a Driving Force For Inflammation-based Carcinomentioning
confidence: 99%